Performance comparison of bolt withdrawal capacity for Mengkulang Glulam / Nor Jihan Abd Malek … [et al.] - Abd Malek, Nor Jihan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2016)
In this study, a glulam as an engineered wood product (EWP) was produced using Mengkulang. The withdrawal capacity tests were conducted on the Mengkulang Glulam using bolts of 12 mm and 16 mm in diameter for parallel and perpendicular grain directions. The results indicated that the withdrawal capacity of 12mm diameter bolt is lower than 16 mm bolt diameter by 80.16% when the bolts are inserted parallel to the grain direction. Meanwhile, the bolt withdrawal capacity for 12 mm is also lower than 16 mm by 64.82% when the bolts are inserted perpendicular to the grain direction. Twelve (12) mm bolt diameter inserted perpendicular to the grain provided higher withdrawal capacity than those inserted parallel by about 62.82%. On the other hand, the withdrawal capacity of 16 mm diameter bolt was observed to be higher in perpendicular to grain direction when compared to parallel insertion which differs by 33.82%. Hence, it can be concluded that the higher bolt diameter provides the better withdrawal capacity. The bolt performs better when it is inserted perpendicular to the grain rather than parallel to the grain directions.